The School manager - Turney, C.; Hatton, N.; Laws, K.; ... [et al.] (Allen and Unwin, 1992)
This book is about: Perspectives on effective schools; Mprale, satisfaction and stress in schools; Leadership styles, skills and technology; Conceptualisting the management process; The planning role; The communicating role; The organising role; The motivating role; The controlling role; ...